Idiopathic Nonspecific Interstitial Pneumonia: Lung Manifestation of Undifferentiated Connective Tissue Disease? - Kinder, Brent W; Collard, Harold R; Koth, Laura; Daikh, David I; Wolters, Paul J; Elicker, Brett; Jones, Kirk D; King, Talmadge E., Jr (American journal of respiratory and critical care medicine, 2007)
The American Thoracic Society/European Respiratory Society International Consensus Classification panel identified the clinical entity idiopathic nonspecific interstitial pneumonia (NSIP) as a provisional diagnosis and recommended further study. We hypothesized that idiopathic NSIP is an autoimmune disease and the lung manifestation of undifferentiated connective tissue disease (UCTD), a recently described, distinct entity. We studied 28 consecutive patients with idiopathic interstitial pneumonia (IIP) enrolled in the University of California, San Francisco Interstitial Lung Disease Center who met prespecified criteria for UCTD, as follows: at least one clinical manifestation of connective tissue disease, serologic evidence of systemic inflammation in the absence of clinical infection, and absence of sufficient American College of Rheumatology criteria for another connective tissue disease. Medical record reviews, evaluation of radiographs, and scoring of lung biopsies were performed. The control group consisted of all other patients (n = 47) with IIP who did not meet the UCTD criteria. The patients with UCTD were more likely to be women, younger, and nonsmokers than the IIP control subjects. Compared with the control group, patients with UCTD-ILD were significantly more likely to have ground-glass opacity on high-resolution computed tomography (HRCT) and NSIP pattern on biopsy, and less likely to have honeycombing on HRCT or usual interstitial pneumonia on biopsy. At our center, the majority of patients classified as idiopathic NSIP (88%) met the criteria for UCTD. Most patients diagnosed with idiopathic NSIP meet the case definition of UCTD. Furthermore, these results show that the clinical entity idiopathic NSIP is different from idiopathic pulmonary fibrosis and appears to be an autoimmune disease.